2018
DOI: 10.29312/remexca.v0i5.1300
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización fisicoquímica de un efluente salobre de tilapia en acuaponia

Abstract: Losobjetivos delestudiofuecaracterizarfisicoquímicamente un efluente salobre de tilapia en producción comercial y evaluar el crecimiento de tres tipos de vegetales herbáceas en acuaponia. El diseño experimental fue completamente al azar. Los intervalos encontrados en los parámetros fueron: temperatura del agua (20-31.5 °C), pH (5.7-7.59), oxígeno (4-5.3 mg L-1), conductividad eléctrica (3.1-8.57 dS m-1), bicarbonatos (0.60-2.60 Meq L-1), cloruros (27-85.7 Meq L-1), sulfatos (2.29-4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
1
4
0
1
Order By: Relevance
“…Another variety of mint, Spearmint, showed the best adaptive response (Espinosa‐Moya, Álvarez‐González, Albertos‐Alpuche, Guzmán‐Mendoza, & Martínez‐Yáñez, ) with greater leaf numbers developed and a greater weight gain per day (AGR), similar to that observed by Salam, Prodhan, Sayem, and Islam () who consider such plants to be highly profitable for certain aquaponic systems. Furthermore, this study corroborates an assertion by (Campos‐Pulido, Alonso‐López, Avalos‐de la Cruz, Asiain‐ Hoyos, & Reta‐Mendiola, ) that plants can achieve greater development in aquaponic systems if the culture period is extended, which would result in greater crop production compared with conventional crop systems. Finally, this study opines that the plants with higher N recovery helped in lowering unionized ammonia and nitrite levels in the cultured water which led to a more appreciable fish growth.…”
Section: Discussionsupporting
confidence: 90%
“…Another variety of mint, Spearmint, showed the best adaptive response (Espinosa‐Moya, Álvarez‐González, Albertos‐Alpuche, Guzmán‐Mendoza, & Martínez‐Yáñez, ) with greater leaf numbers developed and a greater weight gain per day (AGR), similar to that observed by Salam, Prodhan, Sayem, and Islam () who consider such plants to be highly profitable for certain aquaponic systems. Furthermore, this study corroborates an assertion by (Campos‐Pulido, Alonso‐López, Avalos‐de la Cruz, Asiain‐ Hoyos, & Reta‐Mendiola, ) that plants can achieve greater development in aquaponic systems if the culture period is extended, which would result in greater crop production compared with conventional crop systems. Finally, this study opines that the plants with higher N recovery helped in lowering unionized ammonia and nitrite levels in the cultured water which led to a more appreciable fish growth.…”
Section: Discussionsupporting
confidence: 90%
“…Such observed productivity in Sp, suggests that this herb growth is favored by the aquaponic systems, compared to traditional cultivation (Campos-Pulido et al, 2013). However, Ba production obtained in experimental systems is considered high compared with the reported by Carrasco et al (2007) and for the production of Pe.…”
Section: Discussionmentioning
confidence: 72%
“…Spearmint showed the best adaptive response, at the end of the experimental period with greater leaves number developed and a greater weight gain per day (AGR), similar to that observed by Salam, Prodhan, Sayem & Islam (2014) who considers such plants to be highly profitable for aquaponic ra systems. Furthermore, the results suggest that plants can achieve greater development in aquaponic systems if the culture period extends (Campos-Pulido et al, 2013), which would result in greater crop production compared with conventional crop systems. In this sense, it is necessary to analyze how growth factors (temperature and nutrient concentrations) in aquaponic systems affect plants in order to assess their effect on economically important properties as it has been observed that the aquaponic influences the amount of fruit and flavor (Graber & Junge, 2009) that are not always positive, so there must have a control of the water physicochemical parameters according to the plant culture needs (Campos-Pulido et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…El cloruro es un componente común de la mayoría de las aguas y es útil para que los peces mantengan su equilibrio osmótico. El contenido de cloruros en los estanques durante los meses de muestreo, estuvieron dentro de los Criterios Ecológicos de Calidad del Agua (CE-CCA-001/89), que para la protección de la vida acuática se permiten hasta 250 mg/L; así mismo, estuvieron en el intervalo recomendado para el cultivo de tilapia que debe ser menor de 5 mg/L (Campos-Pulido et al, 2013).…”
Section: Resultados Y Discusiónunclassified